Dampak Work From Home terhadap Produktivitas dan Kesejahteraan Karyawan: Studi Systematic Literature Review - Nabila Nur ‘Aini Husna; Novi Mariskha Fihandari; Rafika Meilia Sari (PPIMAN Pusat Publikasi Ilmu Manajemen, 2026)
Changes in work patterns driven by digital technology development and post-pandemic dynamics have encouraged organizations to implement Work From Home (WFH) as an alternative working system. This policy has attracted considerable attention because it affects employee productivity and well-being, which are essential for organizational performance. However, previous studies have reported inconsistent findings regarding the effectiveness of WFH. Therefore, this study aims to analyze the impact of WFH on employee productivity and well-being. A qualitative approach was employee using the Systematic Literature Review (SLR) method by reviewing 19 scientific articles related to productivity, job satisfaction, work-life balance, and mental health. The findings show that 89,5% of articles reported positive effects of WFH through greater flexibility, work comfort, time efficiency, and improved work-life balance, wich contribute to higher productivity and well-being. Meanwhile, 10,5% identified negative effects due to inadequate work facilities, internet disruptions, burnout, and coordination difficulties. These findings indicate that WFH effectiveness is influenced by technological support, job characteristics, and organizational culture. The study implies that organizations should adopt adaptive work policies, strengthen digital infrastructure, and provide mental health support to optimize employee productivity and well-being.